Electrochemical nucleation and growth model of MoS2 for hydrogen evolution reaction - Venumbaka Maneesh Reddy; Marepally Bhanu Chandra; Saravanan Gengan; Selvakumar Duraisamy (Journal of Analytical Science and Technology, 2024)
Abstract The electrochemical nucleation of MoS2 from a mixture of sodium molybdate dihydrate (Na2MoO4·2H2O) and sodium sulphide (Na2S·xH2O) aqueous solution on Cu substrate has been investigated. The nucleation and formation of molybdenum sulphide were investigated employing cyclic voltammetry and chronoamperometry studies. The experimental i–t curves observed at various overpotentials were compared to theoretical curves derived for the two limiting situations of the 3D instantaneous/progressive nucleation and growth model, as reported by Scharifker and Hills. The outcome of electrodeposition potential on nucleation rate (A) and nucleation density (N) was calculated from the current–time transients and SEM morphology obtained at − 1.1 V (5.75 × 1014 and 1.86 × 1015) was compared with − 0.9 V, − 1.0 V, and − 1.2 V, respectively. The investigation of the initial stages of the transient current–time relationships developed for MoS2 electrodeposition specified that film formation occurred progressively initially and instantaneous nucleation during the course of time. A HPMoS2 with an average size of 5–65 nm was obtained at -1.1 V and exhibited superior performance towards the hydrogen evolution reaction compared to samples obtained at − 0.9 V, − 1.0 V, and − 1.2 V.